Implementasi Manajemen Peserta Didik Kelas Menengah Muslim di SMP IT Bina Umat Yogyakarta - Yuliyati, Erlina (Universitas Pesantren Tinggi Darul 'Ulum, 2020)
This paper is a report from the results of a mini research at Bina Umat IT Junior High School in Yogyakarta which describes the management of Muslim middle class students at Bina Umat IT Middle School. Muslim middle class is a population with routine expenses above 4 million per month. Muslim middle class people are aware that education is very important for their children so that they will try to send their children to superior and quality educational institutions, even though they have to pay higher tuition fees compared to the cost in madrasas or other public schools. Middle class people in this case are parents, hoping that their children will get a good quality education in moral education by being in a favorable intellectual environment. The research method used in this research is a qualitative approach. While the data collection is obtained by observation, interview and documentation, all data are presented in narrative descriptive form. The implementation of the management of Muslim middle class students in IT Bina Umat Middle School includes student recruitment, student grouping, coaching and student development.